The Impact of Muhammad bin Salman's Reforms on Saudi Arabian Women's Lifestyles - Nur Sahratul Jannah; Zaqiatul Mardiah; Faisal Hendra (Dinasti International Journal of Education Management And Social Science, 2025)
The Vision 2030 policy initiated by Muhammad bin Salman has had a great influence on social, cultural, and political life in Saudi Arabia. This policy aims to improve and maintain the stability of the country's economy and free itself from dependence on natural resources, namely oil. This study aims to reveal or identify changes in the lifestyle of Saudi Arabian women after Muhammad bin Salman's reforms and the influence of Saudi Arabian women's policies on the country based on literature that discusses these problems. The approach used in this study is a qualitative approach using literature study methods. Of the 30 literatures obtained from official news websites, journal articles, theses and books, this study uses the theory of modernity and self-identity from Anthony Giddens (1991), which shows that Saudi Arabian women have experienced changes in lifestyle after Muhammad bin Salman's reforms through the Vision 2030 Policy based on cultural, employment, social, and educational aspects that have an impact on improving the country's economy.